Growth rate of speckled snapper Lutjanus rivulatus (Teleostei: Lutjanidae) based on tag-recapture data from the iSimangaliso Wetland Park, South Africa. Issue 1 (22nd April 2016) - Mann, BQ; Lee, B; Cowley, PD
Abstract : The growth rate of speckled snapper Lutjanus rivulatus was investigated using data from a long-term tag-recapture study conducted in the St Lucia Marine Reserve within the iSimangaliso Wetland Park, a World Heritage Site in northern KwaZulu-Natal, South Africa. A total of 1 429 L. rivulatus were tagged and 453 (31.7%) individual fish were recaptured one or more times. Growth rates were modelled from the tag-recapture data using a maximum-likelihood approach. It is shown that L. rivulatus is a slow-growing species with L∞ = 918 mm FL, K = 0.06 and phi-prime (Ø, the growth index) = 2.69. The effects of deep-hooking and multiple captures were tested and this revealed that there was no significant impact on the growth of L. rivulatus . The growth index was lower than that recorded in many other similar congeneric species. Slow growth, coupled with high levels of residency and site fidelity, suggest that this species is vulnerable to exploitation and that a precautionary approach towards future management is appropriate.